Engineering Novel TNFα-armed Oncolytic Viruses for Combination Immunotherapy with SMAC Mimetics - Pichette, Stephanie (Université d'Ottawa / University of Ottawa, 2016)
Small molecular Inhibitor of Apoptosis (IAP) antagonists, known as Smac mimetic compounds (SMCs), are a novel class of anti-cancer drugs currently undergoing clinical trials. SMCs were designed to mimic the function of the pro-apoptotic protein, Smac, which directly depletes cells of cIAP1 and cIAP2, and consequently renders tumour cells sensitive to death in the presence of proinflammatory ligands such as TNFα. The Korneluk lab recently reported that SMCs synergize with the attenuated oncolytic virus Vesicular stomatitis virus (VSVΔ51) by eliciting an enhanced immune response in mice, such that the combined therapy is vastly superior to stand-alone therapies. To improve on this SMC-mediated synergistic response, I generated variants of TNFα-armed VSVΔ51. Due to high ectopic expression of TNFα in infected cells, a five times lower viral dose of TNFα-armed VSVΔ51 combined with SMC treatment was sufficient to improve the survival rate as compared to SMC and VSVΔ51 co-therapy. This improved synergistic response is attributed to a bystander effect whereby the spread of TNFα from infected cells leads to the death of neighbouring, uninfected cells in the presence of a SMC. In addition, the double treatment induced vasculature collapse in solid tumours, revealing another mechanism by which cytokine-armed VSVΔ51 in combination with a SMC can induce cancer cell death. This approach demonstrates great potential for engineered oncolytic virus and SMCs as a new combination immunotherapy for cancer treatment.
Keywords: Cancer; Immunotherapy; Smac mimetics; Oncolytic virus; Vascular shutdwown; TNFα